Phytochemistry of Crustose Lichens from Mount Rossman, Ellsworth Land, Antarctica - Zuniga-Navarro, G; Contreras-Arredondo, R (Elsevier Ltd, 2025)
Lichens are symbiotic organisms that inhabit all climate zones of this planet, including even those in Antarctica, thanks to their sophisticated biochemical machinery. This study investigated the phytochemical composition of three lichen species (Pleopsidium sp., Sarcogyne sp., and Rusavskia sp.) collected from Mount Rossman, Antarctica. We used liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS) to putatively assign key secondary metabolites, including anthraquinones and various depsides and depsidones, important for UV protection and antimicrobial defense. We also quantified the lichens’ sugar profiles by high-performance liquid chromatography with refractive index detection (HPLC-RID) using external standards. Here, we provide new perspectives on how these lichens utilize metabolic strategies to survive under extreme desiccation conditions in their terrestrial environment and highlight their biotechnological and pharmaceutical applications. © 2025 Phytochemical Society of Europe